The roles of FMRP-regulated genes in autism spectrum disorder: single- and multiple-hit genetic etiologies. - Steinberg, J; Webber, C (2013)
Autism spectrum disorder (ASD) is a highly heritable complex neurodevelopmental condition characterized by impairments in social interaction and communication and restricted and repetitive behaviors. Although roles for both de novo and familial genetic variation have been documented, the underlying disease mechanisms remain poorly elucidated. In this study, we defined and explored distinct etiologies of genetic variants that affect genes regulated by Fragile-X mental retardation protein (FMRP), thought to play a key role in neuroplasticity and neuronal translation, in ASD-affected individuals. In particular, we developed the Trend test, a pathway-association test that is able to robustly detect multiple-hit etiologies and is more powerful than existing approaches. Exploiting detailed spatiotemporal maps of gene expression within the human brain, we identified four discrete FMRP-target subpopulations that exhibit distinct functional biases and contribute to ASD via different types of genetic variation. We also demonstrated that FMRP target genes are more likely than other genes with similar expression patterns to contribute to disease. We developed the hypothesis that FMRP targets contribute to ASD via two distinct etiologies: (1) ultra-rare and highly penetrant single disruptions of embryonically upregulated FMRP targets ("single-hit etiology") or (2) the combination of multiple less penetrant disruptions of nonembryonic, synaptic FMRP targets ("multiple-hit etiology"). The Trend test provides rigorous support for a multiple-hit genetic etiology in a subset of autism cases and is easily extendible to combining information from multiple types of genetic variation (i.e., copy-number and exome variants), increasing its value to next-generation sequencing approaches.